Agglomeration and Economic Growth in the Special Region of Yogyakarta (2005-2016) - Wahyu Dwi Artaningtyas; Asih Sri Winarti; Jamzani Sodik (EKO-REGIONAL, 2019)
The economic growth of the Special Region of Yogyakarta (Daerah Istimewa Yogyakarta or DIY) surrounding areas is naturally originated from agglomeration which was driven by the spatial concentration of economic activities including the aspects of space, community level, city scale, and region. This study aims to determine the development and linkages between production agglomeration and population agglomeration to the economic growth that occurs in DIY. The approach used is the estimation method of fixed effect panel data regression using DIY city/regency administration data in 2005-2016.The results showed that population agglomeration had a significant and positive effect on economic growth, while production agglomeration had no effect on economic growth in model I. Whereas in model II, it is known that production and population agglomeration affected economic growth, labor force negatively affected growth, and unemployment positively and significantly affected economic growth. On the other hand, the poverty level and HDI variables have a negative effect on economic growth. Cities/regencies that have a positive fixed cross effect on economic growth are Sleman, Gunungkidul, and Kulonprogo Regency, while Yogya City and Bantul Regency show a negative sign.